The Impact of Transformational Leadership and Organizational Culture on Learning Organization: A Comparative Analysis - Rijal, Sapna (Administration and Management Review, 2009)
Scholars and practitioners have identified transformational leadership and organizational culture as important factors that influence the development of learning organization. Yet few studies have empirically examined the impact of transformational leadership and organizational culture have on learning organization. This study proposes hypotheses to understand the impact of transformational leadership and organizational culture on the development of learning organization. Data was collected from the telecommunication sector and a comparison was drawn between Nepal and India. Results indicate transformational leadership and organizational culture have a positive influence in the development of learning organization. The implication of the findings and possible directions for future research are discussed. Administration and Management Review Vol. 21, No. 1, January 2009, Page 102-118